A ASCENSÃO CELESTIAL DE PAULO DE TARSO: ANÁLISE DE 2 CORÍNTIOS 12,1-10 A PARTIR DA HISTÓRIA DA RELIGIÃO E DA NEUROTEOLOGIA - Nogueira, Sebastiana Maria Silva (2012)
The subject celestial journey , well familiar to the old mediterranean world, is based on the belief that the visionary can cross the boundary between humanity and divinity, a constant characteristic in apocalyptic literature. Old Jewish mysticism was seen as an important dimension of this tradition, that is the reason why the mystics used the term apocalypse to describe the revelation of their experiences. Paul s ascension to heaven, recounted in 2 Cor 12,1-10, is the only first hand account and the best evidence of ecstatic practice of celestial journey in first century Judaism. This text, one of great interest in the studies of New Testament, has been examined in thematic forms that extend from the recognition of the apostle as enjoyable to divinity - what granted him such a heroic achievement - to a punishment experience by the guardians of the celestial gates for finding in him no merit to approach the place of the presence of God. For long time, the studies that prevailed in the academy were those of the theological aspects of the passage, such as the spine in the flesh , the apostolic mission , Paul s opponents , among others. The language of the passage reveals important topics that were not considered together for a coherent interpretation of the text. The use of expressions from the Jewish mystical apocalyptic circle like "caught up", "Third Heaven", "hear unutterable words" and "a thorn for the flesh" by the apostle needs to be investigated for the comprehension of what Paul had in mind while using those terms. Another problem is the omission of the experimental approach described in the passage. The apostle reveals that he lived the experience recounted in 2 Cor 12,1-10. While he was telling the unknown status of his body during the rising, he highlights signs of the altered state of consciousness, an aspect that was not considered in the traditional analysis of the text. These problems are analyzed in this thesis take as instruments of the Religion History and the Neurotheology analysis. Models were built trying to demonstrate a correlation between brain activity and mystical experience. In this respect, we have to point out that the emergence of neurotheology, or spiritual neurology brings a progress to the area of religious experience. Some points of difficult interpretation in pauline text have been clarified under this perspective. The proposal of this study was to build a contextual frame to analyse the ecstatic experience of Paul. The study made it possible to infer that the interdisciplinary approach allows a more appropriate scenario to the understanding and interpretation of the text.